Betaine and nano-emulsified vegetable oil supplementation for improving carcass and meat quality characteristics of broiler chickens under heat stress conditions - Suliman, Gamaleldin M.; Hussein, Elsayed O. S.; Al-Owaimer, Abdullah N.; Alhotan, Rashed A.; Al-Garadi, Maged A.; Mahdi, Jameel M. H.; Ba-Awadh, Hani A.; Qaid, Mohammed M.; Swelum, Ayman Abdel-Aziz (Frontiers in Veterinary Science, 2023)
Introduction This research aimed to examine the effects of water-added betaine (BET) and/or nano-emulsified vegetable oil (MAGO) on carcass and meat quality characteristics of broilers raised under thermoneutral (TN) and heat stress (HS) conditions. Methods On day 21, 640 birds (Ross 308) were randomly assigned to one of two thermal conditions (thermoneutral 22 ± 1°C and heat stress 32 ± 1°C) each containing four treatment groups: Control, BET, MAGO, and a mixture of both (BETMAGO) in a 2 × 4 factorial arrangement (eight groups). Each group has eight replicates, with ten birds each. The birds' carcass and meat quality characteristics were evaluated at 35 days. Results and discussion The dressing percentage, breast, leg, wing, heart, initial pH, color change, cooking loss (CL), water-holding capacity (WHC), shear force (SF), and texture profile with exception of springiness significantly affected by the treatments. The results showed that HS had negative effects on carcass weight and relative weights of the breast, spleen, and heart. Moreover, HS increased dressing percentage, wing, initial pH, final core temperature, initial lightness, WHC, and hardness. Significant differences in interactions between treatments and temperature were observed in the spleen, WHC, and SF. Conclusion Water supplemented with BET effectively improved carcass dressing percentage, breast weight, and meat quality in terms of water-holding capacity and tenderness under HS conditions. More studies on the use of BET and/or MAGO at different levels were recommended.